Sosialisasi Keselamatan Kerja pada Kapal Penangkap Ikan di Kabupaten Karawang - Robet Perangin-angin; Dendi Haris; Beta Indi Sulistyowati; Dian Sutono; Ully Wulandari; Untung Prasetyono; Kadi Istrianto; Suharyanto Suharyanto; Sudirman Adibrata (UKInstitute, 2023)
The need for fisheries resources as a source of animal protein encourages the development of capture fisheries businesses. Not infrequently a fishing business in the field of shipping due to lack of care and work cause human souls to become victims. The spirit of the fishermen to go to sea is the main indicator in increasing capture fisheries production in Karawang Regency. However, it is very unfortunate that this was not followed by the awareness of the fishermen about the dangers of working at sea without using personal safety equipment. Therefore, the Karawang Polytechnic of Maritime Affairs and Fisheries Study Program provides training to fishermen on the importance of safety in shipping. As a form of realization of the contents of the Tridarma of Higher Education and the social responsibility and professionalism of a Higher Education in community empowerment towards equitable development. Socialization of Occupational Safety on Fishing Vessels in Karawang Regency is carried out by lecture, question and answer, and demonstration methods. The training materials provided include positioning exercises and anchoring maps with sea charts in Karawang waters, training in the use of map anchoring equipment sets for shipping, training in the use of red hand flares for safety in emergency conditions, training in the use of parachutes signals for safety in emergency conditions, training in the use smoke signal for safety in emergencies, training in the use of lifebuoys for safety in shipping, and training in the use of life jackets. This community service activity was attended by 15 fishermen who live in Karawang Regency.Abstrak: Kebutuhan akan sumberdaya perikanan sebagai salah satu sumber protein hewani mendorong pengembangan usaha perikanan tangkap. Tidak jarang suatu usaha perikanan dibidang perkapalan karena kurang teliti dalam perawatan dan pekerjaannya mengakibatkan jiwa manusia menjadi korban. Semangat melaut para nelayan adalah indikator utama dalam peningkatan produksi perikanan tangkap di Kabupaten Karawang. Namun sangat disayangkan hal ini tidak diikuti dengan adanya kesadaran para nelayan akan bahaya bekerja di laut tanpa menggunakan alat keselamatan diri. Oleh karena itu Program Studi Teknik Penangkapan Ikan Politeknik Kelautan dan Perikanan Karawang memberikan pelatihan kepada para nelayan akan pentingnya keselamatan dalam pelayaran. Sebagai salah satu bentuk realisasi dari isi Tridarma Perguruan Tinggi dan tanggung jawab sosial serta profesionalisme suatu Perguruan Tinggi dalam pemberdayaan masyarakat menuju pemerataan pembangunan. Sosialisasi Keselamatan Kerja Pada Kapal Penangkap Ikan di Kabupaten Karawang dilakukan dengan metode ceramah, tanya jawab, dan demonstrasi. Materi pelatihan yang diberikan antara lain latihan penentuan posisi dan menjangka peta dengan peta laut di perairan karawang, latihan penggunaan set peralatan menjangka peta untuk pelayaran, latihan penggunaan red handflare untuk keselamatan pada kondisi darurat, latihan penggunaan parachute signal untuk keselamatan pada kondisi darurat, latihan penggunaan smoke signal untuk keselamatan pada kondisi darurat, latihan penggunaan lifebouy untuk keselamatan dalam pelayaran, dan latihan penggunaan life jacket. Kegiatan pengabdian masyarakat ini di ikuti oleh 15 orang nelayan yang tinggal di Kabupaten Karawang.